The financing of health in Vitória (ES): a look at primary care - França, Marilene Gonçalves; Silva, Adriana Ilha da; Zuccolotto, Robson (Argumentum, 2024)
This study examines the financing of health actions and services, and in particular those of primary care, in the municipality of Vitória (ES), for the period 2009 to 2019. This documentary and quantitative research analyses indicators for health financing taken from the Information System on Public Health Budgets. The expenditure represents an average of R$ 5,176.91 per inhabitant/annum, with a decrease of 16.52% in available finances. Despite an increase in revenue generated from its own taxes, there is continuing dependence on constitutional transfers. There was also a decrease in federal resources of 32.48% directed to primary care. The municipality, therefore, faces limitations determined by its fiscal dependency, disharmony between participating federal entities and a reduction of federal public resources for the primary care subfunction.